Sustainability analysis of pelagic fisheries using purse seine at Ujong Serangga Fishing Port, Aceh, Indonesia. Issue 1 (November 2021) - Chaliluddin, M A; Yuliana, M; Rizqi, R; Rizwan, T; Rusydi, I; Nellyana, R; Syahputra, F
Abstract: Analysis of the sustainability of pelagic fisheries using purse seine at the Ujong Serangga fishing port is an analysis to determine the level of fisheries sustainability by maintaining a balance between the level of exploitation and the level of utilization of fish resources. The purpose of this study was to determine the sustainability of pelagic fisheries and the most influential factors on the sustainability of pelagic fisheries. This study applied descriptive method with a survey technique. The analysis used is RAPFISH (Rapid Appraisal for Fisheries). The results of the RAPFISH analysis show that the ecological dimension is at a moderate level of sustainability, the economic dimension is at a less sustainable level, the social dimension is at a sustainable level, while the technological dimension is at a moderately sustainable level. Fishing catch that affect the sustainability of pelagic fisheries with purse seine are the ecological dimension by-catch. The economic dimension, assistance from the government with a score of 18.27 and attributes of working capital sources. The social dimension, fisherman's education and the technological dimension, pre-sale management.